Planar Resonators for Metamaterials - M. Blaha; J. Machac (Radioengineering, 2012)
This paper presents the results of an investigation into a combination of electric and magnetic planar resonators in order to design the building element of a volumetric metamaterial showing simultaneously negative electric and magnetic polarizabilities under irradiation by an electromagnetic wave. Two combinations of particular planar resonators are taken into consideration. These planar resonators are an electric dipole, a split ring resonator and a double H-shaped resonator. The response of the single resonant particle composed of a resonator with an electric response and a resonator with a magnetic response is strongly anisotropic. Proper spatial arrangement of these particles can make the response isotropic. This is obtained by proper placement of six planar resonators on the surface of a cube that now represents a metamaterial unit cell. The cells are distributed in space with 3D periodicity.